Next Gen Pop Gen: implementing a high-throughput approach to population genetics in boarfish (Capros aper). Issue 12 (December 2016) - Farrell, Edward D.; Carlsson, Jeanette E. L.; Carlsson, Jens
Abstract : The recently developed approach for microsatellite genotyping by sequencing (GBS) using individual combinatorial barcoding was further improved and used to assess the genetic population structure of boarfish ( Capros aper ) across the species' range. Microsatellite loci were developed de novo and genotyped by next-generation sequencing. Genetic analyses of the samples indicated that boarfish can be subdivided into at least seven biological units (populations) across the species' range. Furthermore, the recent apparent increase in abundance in the northeast Atlantic is better explained by demographic changes within this area than by influx from southern or insular populations. This study clearly shows that the microsatellite GBS approach is a generic, cost-effective, rapid and powerful method suitable for full-scale population genetic studies—a crucial element for assessment, sustainable management and conservation of valuable biological resources.